Morinda officinalis iridoid glycosides, as an inhibitor of GSK-3β, alleviates rheumatoid arthritis through inhibition of NF-κB and JAK2/STAT3 pathway - Shen, Yi; Bao, Ronghua; Ye, Xinyuan; Li, Heming; Sun, Yiqi; Ren, Qiuru; Du, Jinman; Ye, Tianwen; Zhang, Quanlong; Zhao, Qiming; Han, Ting; Qin, Luping; et al. (Frontiers in Pharmacology, 2024)
Morinda officinalis iridoid glycosides (MOIG) showed potential benefits in the treatment of rheumatoid arthritis (RA), but their exact mechanism has yet to be explored. In this study, we evaluated the effects of MOIG on RA, and explored the potential targets and molecular mechanism of MOIG in RA. The results showed that MOIG significantly alleviated the paw swelling and synovial hyperplasia in type II collagen-induced arthritis (CIA) rats. Moreover, MOIG suppressed proliferation, migration and invasion, the secretion of inflammatory factors, and the expression of adhesion related proteins in tumor necrosis factor (TNF)-α-stimulated fibroblast-like synoviocytes (FLSs). MOIG also inhibited the activation of Janus activating kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) and nuclear factor kappa-B (NF-κB) signaling pathway in FLSs. Interestingly, the plant metabolites in MOIG had a good affinity with glycogen synthase kinase-3β (GSK-3β), and inhibition of GSK-3β attenuated the effects of MOIG on FLSs.Knockdown GSK-3β gene could inhibit the paw swelling and inflammatory indicators, decrease the arthritis score and synovial hyperplasia, reduce the phosphorylation of p65 and STAT3 in AA mice, thereby suppressing the NF-κB and STAT3 signaling activation, and MOIG treatment had no significant effects on adjuvant induced arthritis (AA) mice with si-GSK-3β. The results suggested that MOIG alleviates joint inflammation in RA through inhibition NF-κB and JAK2/STAT3 pathway via suppression of GSK-3β in FLSs, which provides supports for MOIG as a promising therapeutic agent of RA.